Preoperative methylprednisolone increases plasma Pentraxin 3 early after total knee arthroplasty: a randomized, double‐blind, placebo‐controlled trial. (9th November 2017) - Lindberg‐Larsen, V.; Kehlet, H.; Pilely, K.; Bagger, J.; Rovsing, M. L.; Garred, P.
Summary: Preoperative glucocorticoid administration reduces the systemic inflammatory response. Pentraxin 3 (PTX3) is a novel inflammatory marker belonging to the humoral arm of innate immunity exerting a potentially protective host response. This study evaluated PTX3 and other complement marker changes after preoperative methylprednisolone (MP) early after total knee arthroplasty (TKA). Seventy patients were randomized (1 : 1) to preoperative intravenous (i.v.) MP 125 mg (group MP) or isotonic saline i.v. (group C). The outcomes included change in plasma PTX3, mannose‐binding lectin (MBL), ficolins (ficolin‐1, −2 and −3), complement components (C4 and C3), terminal complement complex (TCC) and C‐reactive protein (CRP) concentrations. Blood samples were analysed at baseline and 2, 6, 24 and 48 h after surgery with complete sampling from 63 patients for analyses. MP resulted in an increase in circulating PTX3 compared to saline from baseline to 24 h postoperatively ( P < 0·001), while MP reduced the systemic inflammatory response (CRP) 24 and 48 h postoperatively ( P < 0·001). However, the small postoperative changes in MBL, ficolin‐1, −2 and −3, C4, C3 and TCC concentrations did not differ between groups ( P > 0·05). In conclusion, preoperative MP 125 mg increased circulating PTX3 and reduced the general inflammatory response (CRP) early after TKA, but did not affect other complement markers. Abstract : This study evaluated the inflammatory marker Pentraxin‐3 and other complement marker changes after preoperative intravenous administration of methylprednisolone (MP) early after total knee arthroplasty. MP resulted in an increase in circulating Pentraxin‐3 compared to saline from baseline to 24 hours postoperatively, while MP reduced the systemic inflammatory response (CRP) 24 and 48 hours postoperatively.